2004
DOI: 10.1016/s0023-6438(04)00091-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and chemical quality of ground beef treated with sodium lactate and sodium chloride during refrigerated storage

Abstract: The effects of sodium lactate (NaL) and sodium chloride (NaCl), either alone (30 g/kg) or in combination (20+20 g/kg), on the microbiological and chemical quality of raw ground beef during vacuum-packaged storage at 2°C were investigated. The results showed that addition of NaL alone or in combination with NaCl significantly delayed the proliferation of aerobic plate counts, psychrotrophic counts, lactic acid bacteria and Enterobacteriaceae and extended the shelf life of the product up to 15 and 21 days, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 18 publications
4
31
0
Order By: Relevance
“…The shelf-life of control meat is usually limited by microbial spoilage. Depending on hygiene and preservation conditions, raw beef patties stored aerobically have a shelf-life of around 7-8 days in refrigerated conditions (Sallam and Samejima, 2004;Hayes et al, 2010). The same Table and Figure revealed that a slight higher in TPC value was noticed in control sample when compared with other treatments at zero time of cold storage; which indicated that OP and LP caused sudden lethal effect for microorganisms.…”
Section: Microbiological Propertiesmentioning
confidence: 70%
“…The shelf-life of control meat is usually limited by microbial spoilage. Depending on hygiene and preservation conditions, raw beef patties stored aerobically have a shelf-life of around 7-8 days in refrigerated conditions (Sallam and Samejima, 2004;Hayes et al, 2010). The same Table and Figure revealed that a slight higher in TPC value was noticed in control sample when compared with other treatments at zero time of cold storage; which indicated that OP and LP caused sudden lethal effect for microorganisms.…”
Section: Microbiological Propertiesmentioning
confidence: 70%
“…Tan and Shelef (2002) reported that a combination of NaCl and sodium lactate was more effective than lactates alone in delaying the onset of meat spoilage and its effects on its color and fat stability. Sallam and Samejima (2004) reported the use of sodium chloride in combination with sodium lactate reduced the microbial growth, maintained the chemical quality and extended the shelf life of ground beef during refrigerated storage. Kenawi et al (2009) reported that the use of sodium lactate with or without sodium chloride delayed the proliferation of aerobic bacterial plate count, psychrotrophic bacterial count and lactic acid bacterial count, and extended the shelf life for up to 24 days, compared to 8 days for the control samples.…”
Section: Sugarsmentioning
confidence: 99%
“…Sodium salts of the low molecular weight organic acids; such as acetic, lactic, and citric have been used to control microbial growth, improve sensory attributes and extend the shelf life of various food systems including meat (Maca, Miller, & Acuff, 1997;Sallam & Samejima, 2004), poultry (Williams & Phillips, 1998), and fish (Boskou & Debevere, 2000;Zhuang, Huang, & Beuchat, 1996). In addition to their suppressing effect on the growth of food spoilage bacteria, organic salts of sodium acetate, lactate, and citrate were shown to possess antibacterial activities against various food-borne pathogens including Staphylococcus aureus and Yersinia enterocolitica (Lee, Cesario, Owens, Shanbrom, & Thrupp, 2002), Listeria monocytogenes (Qvist, Sehested, & Zeuthen, 1994), Escherichia coli (Lee et al, 2002;McWilliam Leitch & Stewart, 2002), as well as Clostridium botulinum (Anders, Cerveny, & Milkowski, 1989).…”
Section: Introductionmentioning
confidence: 99%